Predictors of clinical outcomes in traumatic intracerebral haemorrhage: Development of a prognostic scoring model - Riza, Ainul; Syahrul, Syahrul; Zakaria, Iskandar; Hidayat, Imam; Musadir, Nasrul (Faculty of Medicine, Universitas Islam Indonesia, 2026)
Background: Traumatic intracerebral haemorrhage (tICH) is frequently observed as a form of intracranial bleeding that follows traumatic brain injury (TBI).Objectives: This study aims to analyse the Glasgow Coma Scale (GCS) score, haemorrhage volume, leukocyte count, and sodium and potassium levels as predictors of clinical outcomes in patients with traumatic intracerebral haemorrhage and to develop a predictive scoring model based on these variables.Methods: This observational analytic study used a retrospective cohort design in the neurology inpatient room at RSUDZA Banda Aceh between January and March 2025. The study included 80 patients with tICH who met the inclusion criteria. The GCS score, bleeding volume, leukocyte count, and sodium and potassium levels were assessed as predictors. The Glasgow Outcome at Discharge Scale (GODS) was used to evaluate clinical outcomes. A multiple linear regression analysis was used to evaluate the effects of independent variables on clinical outcomes. The model was validated using the Hosmer and Lemeshow tests (p>0.05), showing a good fit between the predicted and observed values.Results: A bivariate analysis indicated significant associations between GCS score, bleeding volume, leukocyte count, sodium, potassium levels, and outcomes (p<0.05). A multivariate analysis identified only GCS score (p=0.010; OR=10.102) and bleeding volume (p=0.034; OR=0.129) as independent predictors. A predictive scoring model was developed from the regression coefficients, with scores ranging from 0 to 7. Higher scores indicate a greater probability of poor outcomes, with a score of 7 corresponding to a 98.7% probability. Conclusion: This study highlights the GCS score and bleeding volume as key predictors of clinical outcomes in patients with tICH, while leukocyte count and sodium and potassium levels remain relevant supportive factors in the clinical context. Further validation in larger, diverse populations is warranted to assess its applicability in various clinical settings.